2012
DOI: 10.5923/j.chemistry.20120201.02
|View full text |Cite
|
Sign up to set email alerts
|

Soap Production from Agricultural Residues - a Comparative Study

Abstract: Four agricultural by-products namely Cocoa pod husk (CPH), Kola pod husk (KPH), Plantain peel (PP), and Orange peel (OP) were examined for their potential as alternative source of potash for soap production. These materials were ashed and the samples were subjected to hot aqueous extraction. Extracts from the ashed samples were characterized of their inorganic elements viz calcium, sodium, potassium and magnesium. Results indicated that these samples contains appreciable amount of potassium, a precursor materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
2
Order By: Relevance
“…These metabolites were known for these biological activities such as: antiviral, antibacterial, anti-inflammatory and analgesic activity (Tsuchiya et al 1996 andOjewole, 2008). Yahaya et al (2012) also revealed the presence of flavonoids, , tannins, glycosides, derivatives quinoniques and alkaloids in crude extract of a plant of the same family (Combretum glutinosum). But in this study, only the alkaloids have not been found in the C. adenogonium leaves extracts.…”
Section: Discussionmentioning
confidence: 98%
“…These metabolites were known for these biological activities such as: antiviral, antibacterial, anti-inflammatory and analgesic activity (Tsuchiya et al 1996 andOjewole, 2008). Yahaya et al (2012) also revealed the presence of flavonoids, , tannins, glycosides, derivatives quinoniques and alkaloids in crude extract of a plant of the same family (Combretum glutinosum). But in this study, only the alkaloids have not been found in the C. adenogonium leaves extracts.…”
Section: Discussionmentioning
confidence: 98%
“…Peneliti lain, Yahaya, dkk (2012) juga melakukan penelitian dengan bahan baku yang sama yaitu limbah kulit coklat yang dibakar dengan insinerator pada 450ºC kemudian diekstraksi selama 1 jam. Filtrat yang dihasilkan memiliki kandungan kalium sebesar 37,44% [17]. Selain itu, Afrane juga melakukan leaching kalium dari abu kulit coklat dengan menggunakan pelarut air.…”
Section: Pendahuluanunclassified
“…Hasil ini menunjukkan bahwa pada abu kulit coklat mengandung unsur alkali yang cukup tinggi. Hal ini sesuai dengan percobaan yang dilakukan oleh Yahaya, dkk., (2012) bahwa kandungan kalium pada kulit coklat yang diperoleh dari ekstraksi adalah 41 % [17]. Hal yang sama juga dilaporkan oleh Esther dkk., (2015) dimana kandungan kalium pada kulit coklat adalah sebesar 40 % [11].…”
Section: Analisis Kadar Kalium Menggunakan Atomic Absorption Spectrosunclassified
“…Soap remains an essential ingredient in modern living, used daily for medicinal, laundry purposes, household cleaning, and personal hygiene (Ajao et al, 2011;Chirani et al, 2021;Richardson and Collins, 2023). Soap is a salt of fatty acids obtained worldwide from mainly agricultural products and by-products such as plant (vegetable) oils (Yahaya et al, 2012). If properly harnessed, majority of plant oils and fat can be treated with strong alkaline solutions to obtain soap.…”
Section: Introductionmentioning
confidence: 99%
“…
Soap is a salt of fatty acids obtained worldwide from mainly agricultural products and by-products such as plant (vegetable) oils (Yahaya et al, 2012). Drying neat soap is one of the key steps in the process of manufacturing bar soap.
…”
mentioning
confidence: 99%